Control and optimisation of hybrid electric propulsion system for light aircraft. Issue 13 (26th April 2018) - Savvaris, Al; Xie, Ye; Wang, Letian; Wang, Siqi; Tsourdos, Antonios
Abstract : The growing economical and environmental pressures have accelerated the research and development of hybrid electric power technology in order to increase aircraft performance and reduce the operating and maintenance costs. There has been a big increase in the electrical power rating on new aircraft entering into service. This study gives an overview of the design and development of a hybrid electric propulsion system for light General Aviation aircraft. The theoretical and practical challenges are reviewed and elaborated firstly. The system architecture design is based on a parallel configuration. The ground test of the developed hardware‐in‐the‐loop system is presented based on a test flight mission.